Yang-Monti Principle in Bridging Long Ureteral Defects: Cases Report and A Systemic Review - Bao, Jun Sheng; He, Qiqi; Li, Yuzhuo; Shi, Wei; Wu, Gongjin; Yue, Zhongjin (Urology Journal, 2017)
Ureteric substitution using the Yang-Monti principle was reported as a modification of simple ileal ureter replacement. During April 2013 to June in 2015, 2 patients underwent ileal ureteral substitution using a reconfigured ileal segment of Yang Monti principle in our clinical center. Some slight modifications were made and then follow-up were carried out up to 12 months. For these 2 cases, no significant intra/post-operative complications occurred. In 1 year follow up, serum creatinine (Scr) and blood urea nitrogen (BUN) of both patients decreased to normal. Glomerular filtration rate (GFR), renogram and pyelogram showed a stable split renal function. To better understand the Yang-Monti principle and potential risks and complications, we conduct an systemic review by searching PubMed, Google Scholar and the Cochrane Library database from January 1996 through June 2016. 10 out of 644 publications were identified, which included 269 patients from cohort studies. The most usual indications for Yang-monti therapy were iatrogenic stricture and retroperitoneal fibrosis. Infection and ileus were indicated as the main short time postoperative complications while the fistula and re- strictures happened in long-term. In general,we believe Yang-Monti Principle is a safer and efficient technique for clinical partial and complete ureteral defects if patients and potential risks could be well prepared.